EXPERIENCE OF APPLICATION OF HYDROACOUSTIC PROFILOGRAPH FOR ESTIMATION OF BOTTOM SEDIMENTS OF LARGE RESERVOIR (the Argazin Reservoir as a Study Case) - Alexander V. Beloborodov; Andrey V. Bogomolov; Anatoliy P. Lepikhin; Yuriy S. Lyakhin (Водное хозяйство России: проблемы, технологии, управление)
The work considers application of the method of sub-bottom profiling of bottom sediments of a large reservoir with the use of modern instruments. Such studies are effective in assessing the volume of bottom sediments and the nature of their occurrence. The use of acoustic profilographers in combination with control sampling of bottom sediments without disruption of their vertical structure (column) enables to obtain at minimum costs the necessary set of initial information for planning of further measures.